The characteristic of sayong paperclay slip for artwork / Mohd Shahrol Hanafi Mohd Raffie - Mohd Raffie, Mohd Shahrol Hanafi (2013)
In this case study, Sayong paper clay slip used is produced by the combination of local Sayong clay and paper pulp in producing ceramic output through casting technique. The purpose of this research is to develop knowledge regarding the character of Sayong paper clay slip and to find out the capability of the slip producing an output. The process involved from preparing Sayong clay slip and Sayong paper clay slip until casting output is produced. Apart of Sayong Clay as main material test, three types of paper pulp which is copy print paper, tissue paper and news print paper will be use in this research. The research involved a series of laboratory test which is rheology test, clay body test after slip casting process and practical test of casting output. The result of basic Sayong clay slip will be the benchmark through out analyzing the character of Sayong Paper Clay and the casting output. From the conducted experiment, dried paper pulp content used up to 4% is capable to produce casting output. In rheology test, it is shown that Sayong paper clay slip had low density but high fluidity level and capable to keep slip liquidity in particular time. The shrinkage, strength, weight loss and water absorption of clay body out put is fluctuated according to the percentage of paper pulp. Practical test on casting output proved that the increment of paper pulp content produced more rough texture on the surface and uneven thickness of an output. From the clay body test, the result also showed that all three types of paper pulp used does not giving any large impact towards the character of casting slip. Sayong paper clay slip is capable to produce ceramics product through casting technique. However it is limited to hollow casting technique only because of its physical texture.